Inequality, globalization, and world politics - Woods, Ngaire; Hurrell, Andrew, 1955- (Oxford scholarship online., 1999)
This text suggests that globalization is creating urgent problems for states and international institutions to deal with and that these organisations are increasingly unsuitable for handling such problems.